Curriculum Transformation of Religious Education in Central Sulawesi: Integration of Theological Disaster Literacy within Religious Teacher Certification Frameworks - Arman (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
Central Sulawesi, particularly the Palu-Koro Fault zone, faces high geological disaster risks. However, religious education in this region is not yet integrated with disaster mitigation needs. This is due to a curriculum dominated by metaphysical-eschatological aspects that tend to be fatalistic, and the absence of integrative modules in Religious Teacher Professional Development (PPG). This condition is exacerbated by low theology-based disaster literacy among educators, causing safety messages to be disconnected from religious narratives in the classroom. Objective: This study aims to formulate a curriculum transformation strategy for religious education by integrating theology-based disaster literacy into PPG modules. It seeks to provide a policy framework for standardizing religious teacher competencies in facing disaster risks in red zones. Methods: This research employs a qualitative approach using policy analysis methods based on William N. Dunn’s theory. Data collection techniques included PPG curriculum documentation studies, field observations in post-disaster madrasahs, and literature analysis of contextual theology and educational resilience. Policy alternative analysis was conducted through scoring criteria for effectiveness, efficiency, and responsiveness. Results: The findings indicate that integrating disaster literacy into PPG modules is the most effective